Sustainable Marine Ecotourism Development Strategy at Barambang and Sibintang Beach, Central Tapanuli Regency - Shofian Nanda Adiprayoga; Husnul Yaqin Harahap; Ronal Kurniawan; Tirta Anugerah; Okta Rizal Karsih (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Riau, 2024)
When the holiday season approaches, local and foreign travellers flock to Barambang Beach's and Sibintang Beach's ecotourism regions, which are well-known tourist destinations. Nonetheless, inadequacies in the administration of ecotourism attractions occasionally result in low weekday and weekend visitor numbers at Barambang and Sibintang beaches. Since local populations rely on ecotourism activities for their livelihoods, this influences such activities but is not felt as much by those communities. The study was conducted in 2022 between July and September. A mixed methodology, along with an explanatory qualitative approach, was used in the study. The significant data used in the analysis came from interviews with a variety of participants as well as assessments of the water quality and ecology. Secondary data from some relevant document sources was gathered in the interim. The data analysis used Willingness to Pay (WTP), Willingness to Accept (WTA), economic potential, and SWOT analysis. The study findings indicate that the development plan can be implemented by including auxiliary facilities, such as signs informing visitors of the location of auxiliary facilities, directions, and the farthest swimming-safe water point. Tourists are also eagerly awaiting the establishment of eco-friendly play facilities. Additionally, the government can enact laws that give local community-run businesses regular direction and funding access